The Standardized Wood Extract of Albizia myriophylla: Its Potential as an Active Ingredient in an Anti-inflammatory Herbal Gel Formulation - Bakasatae, Nazneen; Sangkaew, Warissara; Kunworarath, Nongluk; Ontong, Julalak Chorachoo; Phoopha, Sathianpong; Takahashi Yupanqui, Chutha; Voravuthikunchai, Supayang Piyawan; Joycharat, Nantiya (Planta Medica, 2021)
Albizia myriophylla has been used in Thai folk medicine for treating inflammation-related diseases. The wood of this medicinal plant is traditionally used as a single herbal drug in the form of an aqueous decoction and as a component in several Thai herbal formulations for the remedy of fever, sore throat, and aphthous ulcers. This study aimed to evaluate in vivo the anti-inflammatory potential and possible mechanism of action of the standardized wood extract of A. myriophylla as well as to investigate the anti-inflammatory activity and physicochemical properties of the developed herbal gel formulation containing standardized wood extract of A. myriophylla. Results of quantitative HPLC analysis demonstrated that the standardized wood extract of A. myriophylla contained 22.95 mg/g of 8-methoxy-7,3′,4′-trihydroxyflavone, a bioactive marker compound of A. myriophylla. The standardized wood extract of A. myriophylla (1% w/v) exhibited remarkable inhibition (54.4 – 80.3%) in the croton oil model of topical inflammation at all assessment times, comparable to standard indomethacin (55.3 – 63.6%). Real-time quantitative reverse transcription-polymerase chain reaction was performed to clarify the anti-inflammatory mechanism of standardized wood extract of A. myriophylla, and the result showed that this standardized extract decreased lipopolysaccharide-induced nitric oxide synthase mRNA levels in a dose-dependent manner. The developed herbal gel containing standardized wood extract of A. myriophylla (1% w/w) had good physicochemical characteristics and exhibited potent inhibition (51.4 – 77.8%) of inflammation in a rat ear edema model at all assessment times, comparable to indomethacin gel (33.3 – 40.5%). The notable anti-inflammatory activity of standardized wood extract of A. myriophylla and its developed herbal gel formulation indicates their potential application as natural anti-inflammatory agents.
Keywords: Albizia myriophylla; Fabaceae; herbal gel formulation; inflammation; standardized extract